Short-range order in defective half-Heusler thermoelectric crystals. Issue 5 (29th April 2019) - Xia, Kaiyang; Nan, Pengfei; Tan, Shihua; Wang, Yumei; Ge, Binghui; Zhang, Wenqing; Anand, Shashwat; Zhao, Xinbing; Snyder, G. Jeffrey; Zhu, Tiejun
Abstract : The discovery of short-range order, associated with diffuse bands in electron diffraction patterns, provides new insights into defective half-Heusler thermoelectric crystals. Abstract : Crystalline solids are characterized by periodic structures, resulting in a diverse assortment of crystal structures that exhibit a wide variety of properties. Here we report short-range order, which results in characteristic diffuse bands in electron diffraction patterns, in a series of defective 19-electron half-Heusler compounds for the first time. The co-existence of the vacancy-related short-range order and the crystalline long-range periodic structure makes these defective half-Heusler compounds promising thermoelectric materials with low thermal conductivity and high electrical conductivity simultaneously. This new finding provides important insights into the intrinsic nature of defective HH compounds, and also proposes a possible strategy for tuning the degree of ordering to offer great potential for further improvement of thermoelectrics.